2008
DOI: 10.1111/j.1365-2311.2008.01014.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf mining in the Myrtaceae

Abstract: 1. Leaf mining insects feed within plant tissue and thus have close physical associations with their host plants. Little is known about the evolution of relationships between leaf miners and their host species.2. The prevalence of leaf mining was examined in relation to the phylogeny of a dominant family of Australian plants, the Myrtaceae. Sixty-eight species from the 10 major phylogenetic groups within the family were sampled in south-eastern Australia.3. Fifty-seven per cent of the plant species examined we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
0
12
1
Order By: Relevance
“…The longer pre-oviposition period with Eucalyptus spp. plants may also result from the higher nitrogen content in their leaves [14,24]. However, these parameters can be affected by other factors, because the females of this predator that weigh 95 to 150 mg and 160 to 220 mg had a greater pre-oviposition period (16.53 ± 3.33 and 16.09 ± 2.57 days, respectively) [25] than that observed in the present work.…”
Section: Discussioncontrasting
confidence: 55%
“…The longer pre-oviposition period with Eucalyptus spp. plants may also result from the higher nitrogen content in their leaves [14,24]. However, these parameters can be affected by other factors, because the females of this predator that weigh 95 to 150 mg and 160 to 220 mg had a greater pre-oviposition period (16.53 ± 3.33 and 16.09 ± 2.57 days, respectively) [25] than that observed in the present work.…”
Section: Discussioncontrasting
confidence: 55%
“…2006), and yet at least 45 eucalypt species are mined. In a study of leaf miner presence in the Myrtaceae we found leaf miner presence to be positively correlated with phenol concentration and hypothesized that miners may gain protection from UV radiation and/or experience reduced competition from other herbivores by actively seeking phenol‐rich tissue (Sinclair & Hughes 2008b).…”
Section: The Evolution Of Leaf Miningmentioning
confidence: 99%
“…High incidences and abundances of leafminers on dominant plants have been demonstrated at global, regional, and community levels (Dai et al., 2017). For example, the highest reported abundance and richness values of leaf‐mining insects are found for members of Fagaceae and Myrtaceae (i.e., the most dominant plant families in the Northern and Southern Hemispheres, respectively) (Bairstow, Clarke, McGeoch, & Andrew, 2010; Claridge & Wilson, 1982; Dai, Xu, & Cai, 2014; Dai, Xu, & Ding, 2013; Faeth & Mopper, 1981; Ishida, Hattori, & Kimura, 2004; Kollár & Hrubík, 2009; Lopez‐Vaamonde, Godfray, & Cook, 2003; Nakamura, Hattori, Ishida, Sato, & Kimura, 2008; Opler & Davis, 1981; Sato, 1991; Sinclair & Hughes, 2008a,b). The variation in leafminer species richness among different host plants might be described by the species–area (i.e., leafminer species to host plant area) or species–apparency (i.e., leafminer species to host plant apparency) relationship (Dai et al., 2017; MacArthur & Wilson, 1967; Opler, 1974).…”
Section: Introductionmentioning
confidence: 99%